KONSEP RIBA DALAM KOMPILASI HUKUM EKONOMI SYARI’AH (Studi Analisis Teks Kompilasi Hukum Ekonomi Syari;ah Indonesia) - Sari, Febrina; Daipon, Dahyul (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2018)
Economic and financial issues such as trade (tijarah), rent (ijarah), mortgage (rahn), accounts payable (mudayanah), wages to pay (ujrah) and others related to the basic norms of economic transactions are arranged all in Islam . Allah has reduced sustenance to this world to be used by humans in a way that has been legalized by Allah SWT and is clean of all acts that contain usury. Usury is an additional requirement in a business transaction without the existence of iwadh (equivalent) which is justified by the shari'ah for the addition. Broadly speaking, usury is classified into two; usury of debt and usury debt buying and selling. Usury debt accounts are divided into two, namely; usury qiradh and usury jahiliyah, while usury selling and buying is also divided into two, namely usury fadhal and riba nasi'ah. The rules relating to usury are also widely discussed by the jurists in their books. KHES is the actual form of Islamic law in Indonesia related to Islamic economic activities. So that with the presence of KHES, economic business actors carried out according to shari'ah principles if a dispute occurs, it can be resolved with this KHES reference. KHES has been used as a guideline that replaces Islamic law, namely the Qur'an and hadith. KHES is a syari'ah principle guideline source for Judges in the Religious Court and also for the Syari'ah Arbitration Agency in terms of resolving sharia economic disputes. The problem is that none of the KHES articles deal with usury. The word